Respons Pertumbuhan Vegetatif Tanaman Tebu (Saccharum officinarum L.) Ratoon 1 terhadap Pemberian Kombinasi Pupuk Organik dan Pupuk Anorganik - Suci Cahyani; Albertus Sudirman; Abdul Azis (Jurnal Agro Industri Perkebunan, 2016)
This research conduct to know vegetative growth response of sugarcane Ratton 1 to combination of organic fertilizer and inorganic fertilizer which comprises plant height, leaf length, stem diameter, number of tillers, leaf chlorophyll and N, P, K leaf total content. This research was conducted in September 2014 until February 2015 at State Polytechnic of Lampung teaching farm. The research was arranged in a factorial study using a randomized block design (RBD). The first factor is the four-level rate of organic fertilizer, namely: Oo = 0 kg.ha-1; O1 = 500 kg.ha-1; O2 = 750 kg.ha-1; O3 = 1000 kg.ha-1, and the second factor is three rate of inorganic fertilizer, namely A1 = 0%; A2 = 25%; A3 = 50% of recommended rate in Gunung Madu Plantations. The results showed that the effect of all treatments tested were not significantly affected on plant height, leaf length, stem diameter, number of tillers, and chlorophyll. The value of N obtained the highest results in the treatment rate of 500 kg.ha-1 organic fertilizer + organic fertilizer 50% instigation, the value of P highest rate treatment of 500 kg.ha-1 organic fertilizer + organic fertilizer 25% instigation, the value of K obtained the highest results in treatment rates 1000 kg.ha-1 organic fertilizer + 50% inorganic fertilizer recommendation.Keywords: inorganic fertilizers, organic fertilizer (organic Ghaly), ratoon 1Permalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/45